Mobile-Assisted Language Learning for Vocabulary Development: Insights from Indonesian Pre-Service English Teachers Using HelloTalk - Handayani, Vina; Damayanti, Irma (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2022)
The rapid advancement of digital technology has brought significant transformation to language learning, including through Mobile-Assisted Language Learning (MALL). One of the major challenges for English as a Foreign Language (EFL) learners in Indonesia is vocabulary acquisition. This study aims to describe the use of the HelloTalk application by seventh-semester students of the English Education Program at Universitas Negeri Jakarta (UNJ) to develop their vocabulary mastery, identify the learning strategies they employed, and analyze how their MALL experiences contributed to their teaching practices during the Teaching Practicum (PKM) in Jakarta’s secondary schools. A qualitative exploratory case study design was adopted, involving 12 students who actively used HelloTalk during their practicum. Data were collected through in-depth interviews, indirect observation of HelloTalk chat histories, teaching reflection journals, and supporting documentation. Thematic analysis was conducted to identify patterns in vocabulary learning strategies and the connection between MALL experiences and classroom practices. The findings reveal that students employed various strategies, including contextual inference, paraphrasing, translanguaging, and digital note-taking to enhance word retention. Authentic interaction with native speakers enriched their exposure to idiomatic and contextual expressions, which were later adapted into classroom role plays and simulated conversations. However, learning effectiveness was influenced by time constraints, consistency, and limited integration into lesson plans. This study offers a novel perspective by highlighting the link between MALL experiences and pre-service teachers’ pedagogical practices, an area underexplored in the Indonesian context. Theoretically, it extends applied linguistics discourse on technology-based vocabulary learning; practically, it provides curriculum development insights for 21st-century English teacher education.